The application of 19F NMR spectroscopy for the analysis of fluorinated new psychoactive substances (NPS). (November 2022) - Liu, Cui-mei; Song, Chun-hui; Jia, Wei; Hua, Zhen-dong; Liao, Qi
Abstract: In this study, fluorine-19 nuclear magnetic resonance spectroscopy ( 19 F NMR) served as a highly specific tool for identification of fluorinated new psychoactive substances (NPS) as well as a suitable analytical method for the accurate quantification of fluorinated NPS in different seized samples. In the first part of the study, 19 F NMR spectroscopy of a number of different fluorinated NPS, including 51 synthetic cannabinoids, 8 synthetic cathinones, 7 phenethylamines, 8 fentanyl analogues, and 9 other types of compounds was conducted. The chemical shifts and multiplet of the primary fluorides (RCH2 F), fluorobenzenes (ortho-ArF, meta-ArF, and para-ArF), and trifluoromethylbenzenes (ArCF3 ) were discussed in detail to illustrate the role of 19 F signals as special fingerprints in assisting the structure identification of fluorine-containing NPS. To the best of our knowledge, this study is the largest evaluation of fluorinated NPS compounds by 19 F NMR. The second part of this study dealt with the problems encountered in the 19 F quantification procedure and the criteria to be considered for successful quantification by 19 F NMR. General high field (HF)- and low field (LF)- 19 F qNMR methods for the quantification of fluorinated NPS were established after the thorough discussion of NMR spectrum acquisition and processing parameters such as: transmitter frequency offset (O1P), spin-lattice relaxation time (T1 ), and different baseline correction methods. The limit of quantifications (LOQs) for HF- 19 F qNMR varied between 0.1 mg/mL and 0.2 mg/mL, and for LF- 19 F qNMR varied between 1.0 mg/mL and 2.0 mg/mL. The limit of detections (LODs) for HF- 19 F qNMR varied between 0.03 mg/mL and 0.06 mg/mL, and for LF- 19 F qNMR varied between 0.3 mg/mL and 0.6 mg/mL. Finally, the developed methods were applied for the quantification of fluorinated-NPS in seventeen herbal blends, e-liquid, tablet, and powder NPS seizures. Graphical Abstract: The chemical shifts and multiplet of the 83 types of fluorinated NPS were discussed in detail, which can assist the structure identification the new fluorinated NPS. In addition, this study also discussed the key parameters of 19 F qNMR method and finally developed general HR- 19 F qNMR and LR- 19 F qNMR methods for quantifying all types of fluorinated NPS in different matrixes. ga1 Highlights: Chemical shifts and multiplet of 83 fluorinated NPS are detected and discussed. General HF- and LF- 19 F qNMR methods are established for all fluorinated NPS. Seventeen NPS seizures of different matrixes are quantified by 19 F qNMR methods.